벤처기업의 적자회피를 위한 실제 이익조정과 경영자 과신성향 - 김영철(Young-Chul Kim); 총펑잉(Fengying Cong) (인문사회과학연구, 2022)
· 연구 주제: 본 연구의 목적은 벤처기업을 중심으로 이익조정 의사결정에 영향을 미칠 수 있는 경영자의 과신성향과 적자회피를 위한 실제 이익조정 간의 관련성을 살펴보는 것이다. · 연구 배경: 우리나라 경제의 한 축인 벤처기업의 경우 자원 흐름과 경제적 실질의 왜곡에서 초래될 장기 성과하락 위험성으로 인하여 실제 이익조정보다 발생액 이익조정이 수행될 여지가 높다. 다만, 경영자의 과신성향이 존재하는 경우 미래성과에 대한 낙관적 예측으로 인하여 실제 이익조정에 따른 미래성과의 부정적 영향을 과소평가할 수 있다. 따라서 경영자가 과신성향인 벤처기업의 경우 실제 이익조정을 이익조정의 수단으로 사용할 수 있을 것으로 기대된다. 이러한 기대를 토대로 본 연구는 벤처기업을 중심으로 경영자의 과신성향에 따른 실제 이익조정의 차별적 수행 여부에 대하여 분석한다. · 선행연구와의 차이점: 본 연구는 벤처기업 경영자의 성향에 따라 벤처기업의 이익조정의 선호가 차별적으로 나타날 수 있다는 것을 검증한다는 측면에서 기존 선행연구와 차별점이 있다. · 연구방법: 본 연구의 목적을 달성하기 위하여 벤처기업의 이익조정 유인으로써 Burgstahler and Dichev(1997)의 중요한 이익조정 기준점 가운데 하나로 언급되고 있는 적자회피를 선정하였으며, 경영자가 과신성향을 가지며 적자회피란 이익조정 유인이 있는 집단과 그렇지 않은 집단 간 실제 이익조정의 차별적 수행 정도를 검증한다. · 연구결과: 분석 결과 경영자가 과신성향이 있고 적자회피 유인이 있는 집단은 그렇지 않은 집단보다 실제 이익조정을 수행하는 것으로 나타났다. 이상의 결과는 자원의 흐름과 활동의 왜곡에 민감할 수 있는 벤처기업의 경우 경영자가 과신성향이 있다면 미래성과에 대한 낙관적 예측으로 인하여 실제 이익조정을 수행할 수 있다는 것을 시사한다. · 공헌점 및 기대효과: 본 연구는 경영자의 과신성향이 벤처기업의 이익조정 수단의 선택에 영향을 미칠 수 있다는 것을 실증하고 있다는 점에서 공헌점이 있다. 또한 벤처기업의 실제 이익조정의 수단으로써 매출 활동 및 생산활동의 조정을 활용한 실제 이익조정이 재량적비용 조정에 의한 실제 이익조정보다 선호될 수 있음을 보고하고 있는 점이다. · Research topics: The purpose of this study is to examine the relationship between CEO overconfidence tendency and real-based earnings management to avoid losses on venture firms. · Research background: Venture companies prefer accrual-based earnings management to real-based earnings management due to the risk of long-term performance decline caused by the distortion of resource flow, economic substance. However, CEO overconfidence can optimistically predict future performance and underestimate the negative impact of real-based learning management. Therefore, venture companies with CEO overconfidence can use real-based learning management as a measure of avoiding losses. Based on these expectations, this study empirically analyzes the relationship between CEO overconfidence and real-based learning management to avoid losses, focusing on venture companies. · Differences from prior research: This study differs from previous studies in that it analyzes that the preference of venture companies' earnings management measures may change depending on the propensity of the venture company CEO. · Research method: This study selected losses avoidance as an important earnings management incentive for venture companies and verifies the difference in real-based earnings management between groups with overconfidence and earnings management incentives and those without. · Research results: As a result of the study, groups with CEO overconfidence and incentives to avoid losses perform real-based earnings management. The above results imply that venture companies that may be sensitive to the distortion of resources and activities can perform real-based earnings management due to optimistic predictions of future performance by CEO overconfidence. · Contribution points and expected effects: The contributions of this study are as follows. First, it is demonstrated that CEO overconfidence tendencies can affect venture companies' choice to measure earnings management. Second, it was verified that the adjustment of sales and production activities is used rather than discretionary expenditure as a means of real-based earnings management for venture companies. KCI Citation Count: 0